Understanding 401(k) plans - Ramon P. DeGennaro; Deborah L. Murphy (Federal Reserve Bank of Atlanta, 2004)
Questions about the future of the Social Security system continue to surface. As a result, interest in employer-sponsored retirement plans and other retirement investment options increases. But the restrictions and rules associated with various defined benefit plans such as 401(k), 403 (b), and 457 plans can be confusing, and these plans have risks of their own. The authors explore these plans and explain the need to view retirement savings as only one part of a portfolio.
Keywords: 330; Betriebliche Altersversorgung; Sparen; USA